Transitions Between Healthcare Settings of Hospice Enrollees at the End of Life. - Wang, Shi-Yi; Aldridge, Melissa D; Gross, Cary P; Canavan, Maureen; Cherlin, Emily; Johnson-Hurzeler, Rosemary; Bradley, Elizabeth (Journal of the American Geriatrics Society, 2016)
To characterize the number and types of care transitions in the last 6 months of life of individuals who used hospice and to examine factors associated with having multiple transitions in care.